a EFEKTIFITAS KONSELING DENGAN MENGGUNAKAN ALAT BANTU PENGAMBILAN KEPUTUSAN BER-KB (ABPK) PADA IBU HAMIL DALAM PENGGUNAAN KB PASCA PERSALINAN (KBPP) - NURWITA, ATI (Jurnal Ilmiah Bidan (JIB), 2024)
Unintended pregnancy occurs because of too late postpartum contraceptive use. The intervention can be done is provide family planning counseling at pregnancy. One of the tools in family planning counseling is ABPK. This study was aimed to identify the effectiveness of ABPK when postpartum family planning counseling in trimester III pregnant to decision making in postpartum contraceptive use. This study Posttest only control research design. Sample technique with proportional stratified random sampling with the inclusion and exclusion criteria. The results of the bivariate analysis showed that there were insignificant differences proportion of contraceptive methods selected, both in group 29-32 weeks / early third trimester (p 0.474), group 33-36 weeks/ middle third trimester (p value 0.791) and group 37-40 weeks / final third trimester (p 0, 316). There was a significant difference in the timing of family planning use at group 29-32 weeks / early third trimester (p 0.001) and there was no difference in the timing of family planning use at group 33-36 weeks / middle third trimester (p 0, 118) and group 37-40 weeks / final third trimester (p 0, 070). This finding suggests that the use ABPK in postpartum family planning counseling has not been statistically effective in decision making chose contracepsion. Therefore, a postpartum family planning counseling model can be developed aspect of the media, subject or frequency of counseling during pregnancy.